Regenerated Cellulose Membrane with Different Spacer Arm Length of Diamine Monomer for Membrane Chromatography - Yue , Wei Lee; Syed Mohd Saufi, Tuan Chik (AENSI, 2014)
Packed bed column chromatography is widely used for protein separation. However, it has several limitations such as high pressure drop and long processing times. Membrane chromatography is an alternative technique used for protein separation. Specific monomer can be grafted to uncharged membrane to transform into membrane chromatography material. Optimization of parameters involved during this chemical modification is crucial for the development of high performance membrane chromatography for protein separation. The purpose of this research is to develop anionexchanger membrane chromatography from regenerated cellulose membrane by attaching different spacer arm lengths of diamine monomer. Regenerated cellulose membrane was activated in a solution containing sodium hydroxide (NaOH) and epichlorohydrin (EPI). The membrane was grafted with diamine solution of 1,2-diaminoethane or 1,4-diaminobutane to produce positively charged membrane chromatography. The concentration of NaOH activation from 0.05M to 0.50M and diamine monomer concentration from 0.25M to 2.0M during grafting were studied. The optimum concentration of NaOH was 0.20M which produced anion exchange membrane chromatography with capacity of 0.310±0.033 mgBSA/cm2 membrane. High concentration of diamine monomer at 2.0M 1,4-diaminobutane showed a binding capacity of 0.385±0.027mgBSA/cm2 membrane